Effects of Microwave-Assisted Extraction Conditions on Antioxidant Capacity of Sweet Tea (Lithocarpus polystachyus Rehd.) - Ao Shang; Min Luo; Ren-You Gan; Xiao-Yu Xu; Yu Xia; Huan Guo; Yi Liu; Hua-Bin Li (MDPI AG, 2020)
In this study, the effects of microwave-assisted extraction conditions on antioxidant capacity of sweet tea (Lithocarpus polystachyus Rehd.) were studied and the antioxidants in the extract were identified. The influences of ethanol concentration, solvent-to-sample ratio, microwave power, extraction temperature and extraction time on Trolox equivalent antioxidant capacity (TEAC) value, ferric reducing antioxidant power (FRAP) value and total phenolic content (TPC) were investigated by single-factor experiments. The response surface methodology (RSM) was used to study the interaction of three parameters which had significant influences on antioxidant capacity including ethanol concentration, solvent-to-sample ratio and extraction time. The optimal conditions for the extraction of antioxidants from sweet tea were found as follows-ethanol concentration of 58.43% (v/v), solvent-to-sample ratio of 35.39:1 mL/g, extraction time of 25.26 min, extraction temperature of 50 ℃ and microwave power of 600 W. The FRAP, TEAC and TPC values of the extract under the optimal conditions were 381.29 ± 4.42 μM Fe(II)/g dry weight (DW), 613.11 ± 9.32 μM Trolox/g DW and 135.94 ± 0.52 mg gallic acid equivalent (GAE)/g DW, respectively. In addition, the major antioxidant components in the extract were detected by high-performance liquid chromatography with diode array detection (HPLC-DAD), including phlorizin, phloretin and trilobatin. The crude extract could be used as food additives or developed into functional food for the prevention and management of oxidative stress-related diseases.